The first application of Re–Os dating on Paleoproterozoic Francevillian sediments (Gabon) - Ikouanga, Julie Ngwal’ghoubou; Reisberg, Laurie; Pierson-Wickmann, Anne-Catherine; El Khoury, Anna; Fontaine, Claude; El Albani, Abderrazak (Comptes Rendus. Géoscience)
Understanding the age of geological formations is essential to reconstruct Earth’s history. Nevertheless, dating Proterozoic formations is a real challenge because they are often impacted by tectonic, magmatic or metamorphic phenomena. The sedimentary sequences of the Francevillian Basin are well preserved and have been dated previously using many methods (U–Pb, Ar–Ar, Rb–Sr, ...). Here, we applied the Re–Os dating method for the first time, specifically on the “FB” and “FD” formations containing a high organic matter (OM) content (up to10%). The age obtained, 2103 ${± }$ 11 Ma, is coherent with the previous studies. This data confirms the unusual quality of OM preservation and the chronology of the emergence of multicellular life occurring during the Lomagundi event.